Explorando a criatividade na engenharia de requisitos - Lopes, Amanda Fagundes Gobus (2019)
Increasingly, companies are looking for people who demonstrate the ability to create creative and innovative solutions. However, there are a large number of definitions of creativity, which explore aspects of product, process, environment and others. Software Engineering is considered a creative process because it deals with the development of new products and solutions. Design Thinking aims to explore and create solutions that focus on users needs, promoting a collaborative environment for sharing ideas. In this context, the main objective of this work was to explore creativity techniques in Requirements Engineering to propose more attractive products for its users. To this end, a development process has been proposed that incorporates creativity techniques into Design Thinking, in order to put more emphasis on exploring the problem with users and using creativity when requirements engineering. This process was performed with the Program C extension program development team to solve a community problem. In the solution were applied the techniques of creativity Brainstorming, Sketching, Mind Map and 6 Thinking Hats. Brainstorming and Sketching have proven to be easy-to-apply creativity techniques in meetings to generate more (divergent) creative ideas. The techniques of the 6 Thinking Hats and Mind Map stimulated reflection on the product from different perspectives, taking participants out of their comfort zone. Thus, the positive and negative points of the solution were highlighted, as well as ideas for its evolution were generated.